Alternating crystalline lamellar structures from thermodynamically miscible poly(ε-caprolactone) H/D blends. (26th June 2019) - Li, Lengwan; Arras, Matthias M.L.; Li, Tianyu; Li, Wei; Chang, Dongsook; Keum, Jong K.; Bonnesen, Peter V.; Qian, Shuo; Peng, Xiangfang; Lee, Byeongdu; Hong, Kunlun
Abstract: Thermodynamic interaction and non-isothermal crystallization behavior in a series of protiated (H-) and deuterated (D-) poly(ε-caprolactone) (PCL) blends have been systematically investigated. The blends were thermodynamically miscible in the melt. The Flory−Huggins interaction parameter (χ) between H- and D-PCL segments was estimated. The hydroxyl groups in the PCL chain-ends were found to contribute significantly to the negative χ values. Combined characterization of small-angle X-ray scattering (SAXS) and small-angle neutron scattering (SANS) revealed that upon slow cooling, unique alternating H-rich and D-rich PCL lamellar structures are formed regardless of the blend ratio, which is attributed to the T c difference between H- and D-PCLs. While upon rapid cooling, mixed crystals of H- and D-PCLs are predominantly formed. These results provide insightful information on the melt thermodynamics as well as detailed chain arrangements in lamellar crystals for semi-crystalline H/D polyester blends. Graphical abstract: Image 1 Highlights: Thermodynamic interactions and crystallization behavior of protiated (H) and deuterated (D) PCL blends were investigated. The hydroxyl groups in the PCL chain-ends were found to contribute significantly to the negative χ values. Unique alternating H-rich and D-rich PCL lamellar structures are formed regardless of the blend ratio.